2022
DOI: 10.1016/j.renene.2021.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Clean energy consumption, economic growth, and environmental sustainability: What is the role of economic policy uncertainty?

Abstract: Undoubtedly, energy is indispensable to attain economic development; however, it also generates CO2 emissions, which are the dominant contributor to environmental deterioration and climate change. In this regard, clean energy can help to achieve both sustainable development and environmental sustainability since it comprises non-carbohydrate energy sources that do not or seldom generate emissions. Against this backdrop, this work considers economic policy uncertainty (EPU) and probes the impact of clean energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
71
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 260 publications
(79 citation statements)
references
References 50 publications
7
71
0
1
Order By: Relevance
“…Their findings were consistent with Akadiri et al ( 2019 ), Mensah et al ( 2019 ), Destek and Sinha ( 2020 ), Khan et al ( 2021 ), and Dimnwobi et al ( 2021 ) findings that found a positive and monotonic relationship between GDP and CO 2 . A recent study by Xue et al ( 2022 ) also found that GDP increases CO 2 in France. It is important to note that while these studies are consistent in their findings, they fail to explore the possible existence of the EKC hypothesis in their data.…”
Section: Literaturementioning
confidence: 83%
See 4 more Smart Citations
“…Their findings were consistent with Akadiri et al ( 2019 ), Mensah et al ( 2019 ), Destek and Sinha ( 2020 ), Khan et al ( 2021 ), and Dimnwobi et al ( 2021 ) findings that found a positive and monotonic relationship between GDP and CO 2 . A recent study by Xue et al ( 2022 ) also found that GDP increases CO 2 in France. It is important to note that while these studies are consistent in their findings, they fail to explore the possible existence of the EKC hypothesis in their data.…”
Section: Literaturementioning
confidence: 83%
“…The study provides evidence to support Wang and Su ( 2019 ) and Wang et al ( 2018 ) who found IND and URB upsurges in ED in China and India. Thus, pollution rises rapidly through industrialization and urbanization that focus on increasing material production and conversing of the earth's surface into urban places with little to its effects on the environment (Dasgupta et al 2002 ; Xue et al 2022 ). In terms of diagnostic statistics, the Wald chi 2 values are significant at the 1% level, suggesting that the distribution of the variables fits well with the CO 2 model.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations